2018
DOI: 10.1177/1941738118768812
|View full text |Cite
|
Sign up to set email alerts
|

Return to Play After Multiligament Knee Injuries in National Football League Athletes

Abstract: Multiligament knee injuries significantly affect the ability of a football player to return to sport. ACL and MCL tears are associated with better RTP prognosis compared with ACL and PCL/LCL tears.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(36 citation statements)
references
References 19 publications
1
31
2
2
Order By: Relevance
“…Furthermore, no MCL reconstructions and only 1 MCL repair were performed within this cohort. Bakshi et al 3 examined RTP in NFL players after a multiligament knee injury. Among players with a combined ACL-MCL injury, 70.8% were able to RTP, although the grade of MCL injury was not noted.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, no MCL reconstructions and only 1 MCL repair were performed within this cohort. Bakshi et al 3 examined RTP in NFL players after a multiligament knee injury. Among players with a combined ACL-MCL injury, 70.8% were able to RTP, although the grade of MCL injury was not noted.…”
Section: Resultsmentioning
confidence: 99%
“…For comparative purposes, the mean time for National Football League athletes to RTP after surgery for a multiligament knee injury is 12.7 months. 5 This suggests that there may be potential for significant improvement in RTP times for athletes who undergo UCL reconstruction. Accordingly, one option for improving this recovery time may be to optimize the strength and healing potential of the graft at the time of surgery.…”
mentioning
confidence: 99%
“…A previous study that considered NFL players who underwent surgery for MLKIs reported a 64% rate of return to play in the NFL and even lower rates of return to previous levels of play. 3 This level was significantly lower than the levels seen after ACL reconstruction and was dependent on the specific ligament injury patterns involved. 3 We also acknowledge that it is possible that patients with a low-energy MLKI had higher preinjury activity levels or an increased expectation to return to higher levels of activity, which may explain the finding of higher postoperative activity levels in low-energy MLKI patients.…”
Section: Discussionmentioning
confidence: 82%
“…17 However, other studies looking at sportsrelated MLKIs in elite athletes have demonstrated low rates of return to play in comparison with other orthopaedic surgeries. 3 Despite these studies, prognostic indicators for treatment success for MLKIs remain poorly understood.…”
mentioning
confidence: 99%